Meningkatkan Hasil Belajar PKn Melalui Penerapan Model Pembelajaran TGT di SD Negeri Dawung, Tegalrejo, Magelang - Sulastri Sulastri (Prosiding University Research Colloquium, 2021)
This study was used to determine the impac of using the TGT type of cooperative learningmodel in increasing interest in civics learning. The method used by the author in this studyis a classroom action research method, with the subject of class II students at SD NegeriDawung, Tegalrejo, Magelang with a population of 11 student where sample is taken fromall students. This reserch was conducted with a cycle of planning, implementation andobservation which ended with reflection and the continued by holing deliberations betweenmembers of the collaboration to determine planning and the next cycle. The instrumentused for data collection is through multiple choice questions as many as 20 questions, thematerial used is the values of Pancasila. With the result that the use of the TGT (TeamsGames Tournament) learning model can improved student learning outcomes.